Investigation of spectroscopic, crystallographic, thermal and antioxidant properties of mononuclear dioxomolybdenum(VI) complexes derived from a new symmetric bisthiocarbohydrazone. (15th November 2022) - Kaya, Yeliz
Graphical abstract: The new symmetric bisthiocarbohydrazone ligand and its dioxomolybdenum(VI) complexes were synthesized. Synthesized compounds were characterized using analytic and spectroscopic methods. Thermal characteristics of compounds were studied by thermogravimetric analysis. The single crystal structures of two complexes were resolved by X-ray crystallography. Antioxidant properties of compounds were also examined. Abstract: A new symmetric bisthiocarbohydrazone [1, 5-bis(5-allyl-2-hydroxy-3-methoxybenzylidene)thiocarbohydrazone (H2 L )] was prepared from the reaction of thiocarbohydrazide with 5-allyl-2-hydroxy-3-methoxybenzaldehyde. Five new solvate dioxomolybdenum(VI) complexes of close formulas [MoO2 (L)R-OH] (R: methyl for Mo1, ethyl for Mo2, propyl for Mo3, butyl for Mo4 and pentyl for Mo5 ) were synthesized by reacting bis(acetylacetonato)dioxomolybdenum(VI) [MoO2 (acac)2 ] with this proligand H2 L. The structures of all compounds were verified by IR, UV–vis and 1 H NMR spectroscopies, elemental analysis, magnetism and molar conductivity measurings. The solid-state structures of Mo1 and Mo2 were also elucidated using the X-ray crystallography technique. X-ray crystallographic studies indicated that symmetric bisthiocarbohydrazone is coordinated to the cis -MoO2 2+ ion through sulfur atom, imine nitrogen and phenolic oxygen as the tridentate ONS donor. The sixth coordination of the molybdenum atom, which has distorted octahedral geometry around it, is completed by solvent (R-OH). The thermal characteristics of the compounds were studied by thermogravimetric analysis (TGA). TGA results support the presence of solvent molecules coordinated to molybdenum atoms in the complexes. Antioxidant capacities of the compounds were measured using the CUPric Reducing Antioxidant Capacity (CUPRAC) method. The compounds were also examined for their free radical scavenging activities by the 2, 2-diphenyl-1-picrylhydrazyl (DPPH) free radical method. When compared to a standard, Trolox, all of the compounds demonstrated good antioxidant activity.